Preventive and therapeutic effect of vitamin D on depression-like behavior in a mouse adolescent depression model and its association with BDNF protein expression - Yang, Xueping; Miao, Junxiao; Huang, Yinglin; Li, Lili; Zhuang, Gengsen (Frontiers in Psychiatry, 2024)
Adolescence is an important period of psychological development, a stage of continuous growth and dynamic change. Physiological, psychosocial, and cognitive changes make adolescents susceptible to psychological disorders. Depression is a psychological disorder with a high incidence and is the leading cause of disability worldwide. A meta-analysis showed that the global point prevalence of depression was 34% between 2001 and 2020 based on self-reported depressive symptoms.The point prevalence of major depressive disorder (MDD) and dysthymia was 8% and 4%, respectively. Furthermore, depressive symptoms in adolescents increased from 24% between 2001 and 2010 to 37% between 2011 and 2020. The Middle East, Africa, and Asia have the highest prevalence of elevated depressive symptoms. [1] Since depression typically begins in adolescence, juvenile cases are more likely to be first cases, while adult cases may be relapses from earlier juvenile cases. Symptomatic characteristics differ between adults and adolescents. Autonomic dysregulation symptoms (insomnia, fatigue, and changes in appetite and weight) are more common in adolescents with MDD than in adults. Further, anhedonia/loss of interest and concentration problems are more common in adults with MDD.